The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ijo.2015.2910
|View full text |Cite
|
Sign up to set email alerts
|

ACK1 promotes hepatocellular carcinoma progression via downregulating WWOX and activating AKT signaling

Abstract: Abstract. Several studies have revealed that ACK1 is upregulated in various cancers and promotes tumor progression. However, the role and mechanism of ACK1 in hepatocellular carcinoma (HCC) remains unknown. In this study, the expression of ACK1 was assessed in several cell lines and 150 pairs of HCC and adjacent noncancerous liver tissues. The protein expression of p-ACK1 and WWOX were detected by immunohistochemistry to evaluate their correlation with ACK1. Flow cytometry, caspase 3/7 activity assay, BrdU cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…We also found associations between ACK1 expression and dysplasia grade in both types of precursor lesions for CRC. This is in accordance with studies of several other tissues which showed ACK1 expression correlated with malignant progression [26]. By contrast, we found both UC-related CRC and sporadic CRC were negative for ACK1 protein expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also found associations between ACK1 expression and dysplasia grade in both types of precursor lesions for CRC. This is in accordance with studies of several other tissues which showed ACK1 expression correlated with malignant progression [26]. By contrast, we found both UC-related CRC and sporadic CRC were negative for ACK1 protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…Although Ack1 overexpression has been observed in multiple cancers, including digestive system tumors, most functional studies of ACK1 signaling pathways are focused on the respiratory and reproductive system [25]. Our study revealed extensively increased expression of ACK1 protein in colorectal inflammation and dysplasia, but the potentially functional role and molecular mechanism for ACK1 overexpression in these colorectal diseases are currently completely unknown.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…WWOX is a type of tumor suppressor gene and is linked with the FRA16D common chromosomal fragile site 15. Furthermore, researchers found that it was associated with many cancers, including EOC,16 hepatocellular carcinoma,17 and colon cancer,18 bladder cancer,19 osteosarcoma,20 and other cancers. In EOC, WWOX plays significant roles in the regulation of the cell cycle and apoptosis 16.…”
Section: Introductionmentioning
confidence: 99%
“…6). ACK1 has been implicated previously in hepatocellular carcinoma metastasis (38). We observed a decrease in the random motility of T cells upon exogenous ACK1 expression compared with wild-type cells on ICAM-1-coated plates (Fig.…”
Section: Resultsmentioning
confidence: 96%